Production and Financial Analyses of Integrated Rice-Fish Farming in a Smallholders Community in Teluk Intan, Perak, Malaysia - Adji Syahputra, Bambang Surya (2006)
The study was initiated to investigate production and financial analyses of integrated rice-fish farming system on smallholders’ in Teluk Intan, Perak, Malaysia. Specifically, the objectives of the study were to determine farmers’ income and financial analyses of integrated rice-fish farming system on the distribution of household income in the sample area. Questionnaires were distributed to smallholders around Sungai Manik and Labu Kubong in Teluk Intan. Three types of farmers were included in this study, namely those practiced rice farming system, integrated rice-fish farming system and fish farming within the rice field system. The study was conducted in three consecutive growing seasons from 2002 – 2004 which fish Barbodes gonionotus were introduced in densities, namely 2000, 4000, 6000, 8000 and 12000 fingerlings per hectare. Fish were not given supplementary food, except in the third season of were commercial feed were also given. The result had shown that the Rate of Return on Operational Cost (RROC) for integrated rice-fish farming (75.18%) was higher than rice farming only (41.32%) and also higher than the fish farming only (59.2%) only. Net income per hectare per season from rice-fish farming (RM 1,706.68) was also higher than that rice farming only (RM 1,046.64). Apart from that, rice farming system also incurred high fertilizer (32.26%) and pesticides (25.38%) costs. Rice-fish farming system, on the other hand, incurred high fertilizer (31.4%) and fingerlings (20.09%) costs. The present study, utilizes the Cobb-Douglas production function to estimate the production functions for different farming systems. Results of the regression analyses showed that a 10% increase in the amount of fertilizer rate would increase rice output by 21.25% in the rice-fish farming. In the rice only, the same increase in amount of fertilizer rate would increase rice output by only 0.06%. The result showed that Specific Growth Rate (SGR) of the fish tends to decrease throughout the experimental seasons. The fish also tends to get smaller throughout the harvesting season. The growth of fish was best at 42 days after release, which was 1.92% of bodyweight/day. The fish differed significantly in term of length and body weights when treated with different types of feed. The RROC of integrated rice-fish farming system at lower stocking densities, namely 2000 and 4000/ha were 39.83% and 27.81%, respectively, and this were higher than that of rice farming system (25.47%). Similarly, net ricefield income of rice-fish farming system of RM 890.64 and RM 671.68 at lower stocking densities of 2000 and 4000/ha respectively, were also higher than that of rice farming system (RM 631.40). However, at higher stocking densities, the cost of purchasing fingerlings would be higher than the costs of pesticides, which would result in lower RROC for the integrated rice-fish farming system as compared to rice only. Essentially, the integrated rice-fish farming system is not a system that requires additional input capital, but merely a system that substitutes the cost of purchasing pesticides with the cost of purchasing fingerling.